Brucine: A Review of Phytochemistry, Pharmacology, and Toxicology - Lu, Lu; Huang, Rui; Wu, Ye; Jin, Jin-Mei; Chen, Hong-Zhuan; Zhang, Li-Jun; Luan, Xin (Frontiers in Pharmacology, 2020)
Brucine, a weak alkaline indole alkaloid, is one of the main bioactive and toxic constituents of Nux-vomica. Modern pharmacology studies and clinical practice demonstrate that brucine possesses wide pharmacological activities, such as anti-tumor, anti-inflammatory, analgesic and the effects on cardiovascular system and nervous system, et al. However, its central nervous system toxicity severely limits its clinical application. Herein, the physicochemical properties, pharmacological activities and toxicity of brucine were reviewed, and the novel strategies to address the toxicity issues were discussed, aiming to bring new insights into further research and application of this active component.